Answer:
Your equation is
![(x - (5))^2 + (y - (6))^2 = (√(13) )^2](https://img.qammunity.org/2023/formulas/mathematics/college/gjw37t2suicx0r7748pu0i84qv5qfomk3d.png)
Explanation:
Well, the center origin of the circle is given (h,k) = (5,6).
We have to find our radius as they gave us a point. from origin to the edge of the circle.
Using the formula: (x - h)^2 + (y - k)^2 = r^2
Plug in our (h,k) = (5,6) and (x,y) = (7,9) to solve for radius.
(x - h)^2 + (y - k)^2 = r^2
(7 - (5))^2 + (9 - (6))^2 = r^2
(2)^2 + (3)^2 = r^2
4 + 9 = r^2
r^2 = 13
r = sqrt(13)